Optimization of Broiler Feed Production from Corn Husk Waste by Aspergillus niger, Trichoderma viride and its Consortium - Ningrumsari, Ida; Budiasih, Rd. (Pakistan Journal of Nutrition, 2015)
The aim of this study was to determine the dose of inoculum and fermentation period by A. niger, T. viride and its consortium on the waste of corn husk to get the best substrate nutrient content (crude protein, crude fat and crude fiber). The experiment was arranged in a Completely Randomized Design (CRD) with three replications. The first factor is the type of microbe (M) which consists of three levels, i.e., A. niger (m1). T. viride (m2), A. niger+T. viride (m3). The second factor is the inoculum dose (D) consists of three levels, i.e., d1 = 2 g, d2 = 3 g and d3 = 4 g. The third factor is the period of fermentation (W) is w1 = 48 h, w2 = 76 h and w3 = 96 h. The existing data collected and processed by Variance Analysis (ANOVA). If there is a significant difference to the control, then followed by Duncan’s multiple range test. The results showed that the increase of crude protein present in the interaction between types of microbes and dose of inoculums, that is consortium microbe of 15.40%. The interaction between microbes and fermentation period on consortium microbe is 18.38% in 96 h, while the average decline in crude fiber influenced by microbes present in T. viride is 1.81%. The decline average of crude fiber influenced by fermentation period of 48 h is 0.54%. The decline average of crude fat which influenced by consortium microbe type (5.75%) while the average of crude fat reduction influenced by inoculum dose is at the dose of 0.2% (b/k).